Practical guideline for the restructuring of enterprises involving consulting services (on the example of Ukrainian industrial enterprises) - Anatoliy Kovalyov; Olha Vynokurova (European Financial and Accounting Journal, 2017)
The article examines the role of consulting services in the restructuring of enterprises. It describes how consulting firms help to increase the efficiency of enterprises and their value by providing information and recommendations. The work grounds the importance of the restructuring implementation adaptation for enterprises to external market conditions in order to increase their value and improve efficiency, competitiveness and market activity. The authors describe the stages of the restructuring and the participation of a consulting firm at each stage. The work shows the methodology of the restructuring with the involvement of consulting services. Our theoretical arguments are supported by case from the experience of the auditing company has conducted the restructuring in industrial enterprise. The example of implementation the restructuring of the organizational structure of the industrial holding in Ukraine through the services of an auditing company is given. This paper provides an effective way of the restructuring acceptable not only for industrial companies in Ukraine but also for enterprises that operate in a transitional economy.
Keywords: G34; 650; Adaptation; Company's value; Consulting services; Diagnostics of companies; Restructuring